IMPACT OF GST ON SMALL AND MEDIUM ENTERPRISES (SMES) IN INDIA - Riya Goel; Prof.V.N.Sharma (International Educational Journal of Science and Engineering, 2025)
The introduction of the Goods and Services Tax (GST) in India in 2017 aimed to unify the country’s indirect tax system and create a single national market. This paper examines its impact on Small and Medium Enterprises (SMEs), which contribute nearly 30% to India’s GDP and employ over 110 million people. Using descriptive and analytical methods, the study highlights both opportunities and challenges arising from GST. Findings indicate that while GST reduced tax cascading, improved transparency, and encouraged digital adoption, it also imposed a disproportionate compliance burden on micro enterprises. Delays in input tax credit refunds created significant working capital stress, whereas digitally capable medium firms benefitted from improved interstate trade and stronger turnover growth. The paper concludes with policy recommendations such as simplified compliance procedures, faster refund processing, and digital support measures to ensure GST becomes more inclusive and SME-friendly.